Lenny Krayzelburg's Full Stroke at 35 m of His 100 m Backstroke Gold Medal Swim at the 1997 Pan Pacific Championships, Fukuoka, Japan - Rushall, B. S. (1999)
Video pictures (15 frames) and the appropriate technical/ biomechanical explanations for Lenny Krayzelburg's Full Stroke at 35 m of His 100 m Backstroke Gold Medal Swim at the 1997 Pan Pacific Championships, Fukuoka, Japan. Lenny Krayzelburg's stroke demonstrates all the factors of effective, modern backstroke swimming. His streamlining is consistent with head and shoulders down, hips up, and the hips and shoulders rotating together. Both arm pulls feature early and direct force pplication in the stroke cycle which goes through a transition to produce a powerful inward and upward scull in the latter phase of the stroke. This swimmer's stroke is the most symmetrical, balanced, and modern of backstroke techniques.